2021
DOI: 10.3390/ijms22147423
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Molecule 5-Pyridoxolactone Identified Post BmNPV Infection of the Silkworm, Bombyx mori

Abstract: Bombyx mori nucleopolyhedrovirus (BmNPV) is a pathogen that causes great economic losses in sericulture. Many genes play a role in viral infection of silkworms, but silkworm metabolism in response to BmNPV infection is unknown. We studied BmE cells infected with BmNPV. We performed liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS)-based non-targeted metabolomics analysis of the cytosolic extract and identified 36, 76, 138, 101, 189, and 166 different molecules at 3, 6, 12, 24, 48, and 72 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
(59 reference statements)
2
7
0
Order By: Relevance
“…A previous study revealed that, when Sf9 ( Spodoptera frugiperda ‐9) cells were infected with the recombinant baculovirus, the purine synthesis pathway was activated and the uric acid content increased (Guillemin et al, 2020). This phenomenon was also observed in silkworms after BmNPV infection (Feng et al, 2021; Hua et al, 2021), as well as in this study, but the underlying mechanism remains unclear. In the process of uric acid synthesis, XO is an essential enzyme responsible for the conversion of hypoxanthine to uric acid and the production of H 2 O 2 during this process, which further causes ROS (Kimura et al, 2021; Odake et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A previous study revealed that, when Sf9 ( Spodoptera frugiperda ‐9) cells were infected with the recombinant baculovirus, the purine synthesis pathway was activated and the uric acid content increased (Guillemin et al, 2020). This phenomenon was also observed in silkworms after BmNPV infection (Feng et al, 2021; Hua et al, 2021), as well as in this study, but the underlying mechanism remains unclear. In the process of uric acid synthesis, XO is an essential enzyme responsible for the conversion of hypoxanthine to uric acid and the production of H 2 O 2 during this process, which further causes ROS (Kimura et al, 2021; Odake et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…A previous study revealed that, when Sf9 (Spodoptera frugiperda-9) cells were infected with the recombinant baculovirus, the purine synthesis pathway was activated and the uric acid content increased (Guillemin et al, 2020). This phenomenon was also observed in silkworms after BmNPV infection (Feng et al, 2021;Hua et al, 2021), as well as in this study, but the underlying mechanism remains unclear.…”
Section: Uric Acid Pathway Inhibits Bmnpv By Activating Apoptosissupporting
confidence: 75%
“…LC–MS/MS analysis indicated that in BmE cells at different infection stages (3 ~ 72 hpi), metabolite pathways were concentrated in ABC transporter, amino acid transport RNA, and purine metabolism signaling pathways ( Hua et al, 2021 ). Cluster analysis was gathered in 5-pyridoxolactone, GPC, 2-OH-Ade, γ-Glu-Cys, and hydroxybutyramide, which all showed a constant upregulation in these periods ( Hua et al, 2021 ). At the same time, only 5-pyridoxolactone strongly inhibited BmNPV replication in the phenotype experiments ( Hua et al, 2021 ).…”
Section: Multi-omics Analysis Of Bmnpv-associated Genesmentioning
confidence: 99%
“…Cluster analysis was gathered in 5-pyridoxolactone, GPC, 2-OH-Ade, γ-Glu-Cys, and hydroxybutyramide, which all showed a constant upregulation in these periods ( Hua et al, 2021 ). At the same time, only 5-pyridoxolactone strongly inhibited BmNPV replication in the phenotype experiments ( Hua et al, 2021 ). It is shown that metabolites may have a complex resistance mechanism to BmNPV.…”
Section: Multi-omics Analysis Of Bmnpv-associated Genesmentioning
confidence: 99%
See 1 more Smart Citation